Identification of Proteins Deregulated by Platinum-Based Chemotherapy as Novel Biomarkers and Therapeutic Targets in Non-Small Cell Lung Cancer - Ryan, Sarah-Louise; Dave, Keyur A.; Beard, Sam; Gyimesi, Martina; McTaggart, Matthew; Sahin, Katherine B.; Molloy, Christopher; Gandhi, Neha S.; Boittier, Eric; O’Leary, Connor G.; Shah, Esha T.; Bolderson, Emma; et al. (Frontiers in Oncology, 2021)
Platinum-based chemotherapy remains the cornerstone of treatment for most people with non-small cell lung cancer (NSCLC), either as maintenance therapy or in combination with immunotherapy or targeted therapies. However, resistance to therapy remains a primary issue. Hence, predictive biomarkers and novel combinational strategies are required to improve the effectiveness and durability of treatment response for people with NSCLC. The aim of this study was to identify novel biomarkers and/or drug targets from protein networks involved in the cellular response to cisplatin. Following exposure of NSCLC cells to cisplatin, in vitro quantitative SWATH mass spectrometry was applied to identify altered protein response networks. A total of 65 proteins were significantly deregulated following cisplatin exposure. These proteins were assessed to determine whether these proteins were druggable using novel machine learning approaches and to identify whether these targets might serve as prognosticators of platinum therapy. Our data demonstrate novel candidates and drug-like molecules warranting further investigation to improve response to platinum agents in NSCLC.